Worship Beyond Ritual: The Role of Ibadah in Shaping Ethical and Spiritual Life in Islam - Hariati; Nurmawaddah; M. Amin (Masterpiece, 2026)
Worship (ibadah) constitutes the core of Islamic teachings and serves as a comprehensive expression of faith that extends beyond ritual practices. This article aims to explore the role of ibadah in shaping ethical and spiritual life in Islam by emphasizing its holistic nature, which integrates spiritual devotion, moral discipline, and social responsibility. Using a qualitative conceptual approach, this study draws upon classical and contemporary Islamic sources, including Qur’anic verses, Prophetic traditions, and the scholarly works of Ibn Taymiyyah, Al-Ghazali, Fazlur Rahman, and Quraish Shihab. The analysis reveals that ibadah in Islam encompasses both ritual and non-ritual dimensions, encompassing acts of worship performed through the heart, speech, physical actions, and the use of wealth, all of which are guided by sincere intention (niyyah). These practices function not only as means of spiritual connection with God but also as mechanisms for cultivating ethical awareness, self-discipline, social solidarity, and responsible conduct in everyday life. Furthermore, the study highlights the contemporary relevance of ibadah in addressing moral and spiritual challenges associated with modernity, such as materialism, individualism, and the erosion of ethical values. By framing ibadah as a form of worship that transcends ritual boundaries, this article contributes to a deeper understanding of Islamic worship as a foundational element in fostering ethical integrity and spiritual well-being within modern Muslim society